The effects of financing rules in pay-as-you-go pension systems on the life and the business cycle - Christian Scharrer (Universität Augsburg, Institut für Volkswirtschaftslehre, 2020)
I study the impacts of financing rules for financial surpluses in pay-as-you-go pension systems on the business cycle and the life cycle in a dynamic stochastic large-scale overlapping generations model, where households take the inter-temporal links between contributions and pension benefits explicitly into account. The results point out that sluggish adjustments of contribution rates that are implemented by adjusting a financial buffer stock both stabilize an economy and decrease the volatility of life-time utilities of retirees and workers close to retirement. Such a policy allows these households a better hedge against macroeconomic shocks over the business cycle. Moreover, I show that the impacts of higher fluctuations of aggregate variables on the volatility of individual lifetime utilities can rather be negligible.
urn:nbn:de:bvb:384-opus4-1026291
Keywords: H55; E21; E30; 330; Overlapping Generations; Pay-As-You-Go Pension Systems; Financing Rules; Business Cycle; Life Cycle; RBC-Model